Effects of intumescent flame retardant based on THEIC-based oligomeric ester as char forming agent on thermal，mechanical and flame retardant properties of HDPE composites - Khanal, Santosh (Journal of Nepal Chemical Society, 2022)
In this study, a new phosphor-ester (TPE) was prepared by one-spot polycondensation of tris (2-hydroxyethyl) isocyanurate (THEIC) and phenyl phosphonic dichloride (PPDC) and used as a charring agent in combination with ammonium polyphosphate (APP) to develop new intumescent flame retardant (IFR) for high-density polyethylene (HDPE). The thermal and flame retardant properties of composites were investigated by thermogravimetric analysis (TGA), limiting oxygen index measurement (LOI), and cone calorimetry (CCT). At the same time, the morphology and chemical structure of the char residue were analyzed by scanning electron microscopy, Fourier transfer infrared spectroscopy, and laser Raman spectroscopy. The results showed the LOI value of the composite HD/APP/TPE containing 25 wt. % of APP/THE reaches 28.2 %. The CCT test suggested that the peak heat released rate (PHRR) of the flame retardant composite is decreased by 37 % compared to that of pure HDPE. The use of IFR based on APP and TPE produces a compact char residue that acts as a barrier for heat, oxygen, and volatile combustibles and protects the underlying polymer. Besides TPE can produce the PO-type radicals that show some gas phase flame retardant action. However, the tensile strength of the composites is still lower than that of pure polymer.